Effects of Moxa Cone Moxibustion Therapy on Cognitive Function and Brain Metabolic Changes in MCI Patients: A Pilot 1H-MRS Study - Mai, Wei; Zhang, Aizhen; Liu, Qiang; Tang, Liying; Wei, Yichen; Su, Jiahui; Duan, Gaoxiong; Teng, Jinlong; Nong, Xiucheng; Yu, Bihan; Li, Chong; Shao, Lijuan; et al. (Frontiers in Aging Neuroscience, 2022)
Objective: To examine the effect of moxa cone on N-acetylaspartate (NAA), total creatinine (tCr) and choline (Cho) in the bilateral hippocampus (HIP) and bilateral posterior cingulate gyrus (PCG) in patients with mild cognitive impairment (MCI) using 1H-MRS and to provide imaging basis for moxa cone moxibustion prevention and treatment for MCI. Methods: Sixty-nine patients with MCI and 67 age-matched normal controls were enrolled. MCI patients were randomly divided into drug group (n=24), acupoint group (n=25) and sham point group (n=20). The drug group was treated with oral donepezil hydrochloride. The acupoint group and sham point group received moxa cone moxibustion treatment. MMSE and MoCA scores were recorded before intervention, after 1, 2, 3 months of intervention. The ratio of NAA/tCr and Cho/tCr in the bilateral HIP and bilateral PCG were measured by 1H-MRS before and at the end of the intervention. Results: Before treatment, compared with the normal control group, the MMSE scores and MoCA scores, the value of NAA/tCr in the bilateral HIP, the value of Cho/tCr in the right HIP, as well as the value of NAA/tCr in the left PCG were significantly decreased in the three treatment groups (both P < 0.01); the value of NAA/tCr in the right PCG were significantly decreased in the acupoint and drug groups (P < 0.05). After two months of treatment, there were no significant differences in the MoCA scores, the value of NAA/tCr and the value of Cho/tCr in both the bilateral HIP and PCG in the three treatment groups compared with the normal control group (P > 0.05). The MMSE scores and MoCA scores at all time points in the acupoint and sham point groupswere higher than those in the drug group, which were similar to those in the control group. Conclusion: Moxa cone moxibustion may improve the cognitive function of MCI patients by regulating the abnormal metabolites of the bilateral HIP and bilateral PCG. MRS can provide objective imaging basis for moxibustion prevention and treatment of MCI. Trial Registration: www.chictr.org.cn, ChiCTR-IPR-16009144.